A new genus and species of sepiolid squid from the waters around Tonga in the central South Pacific (Mollusca: Cephalopoda: Sepiolidae) - Lu, C. C.; Boucher-Rodoni, R. (Zootaxa, 2006)
A new genus and species, Choneteuthis tongaensis gen. et sp. nov., is described from the waters around Tonga in the central South Pacific Ocean. The new genus does not clearly fit in any of the currently recognized subfamilies of the family Sepiolidae, justifying a reconsideration of the subfamilial subdivision of the family.